Study on the Equiralent Elastic Properties of Two Kinds of Lattice Material Uimicking by Metal Crystal Structures - Lu GUO; Guiying WU; Zhihua WANG (Taiyuan Ligong Daxue xuebao, 2022)
On the basis of metal crystal structures, the theoretical models of effective elastic Young's modulus of body centered cubic (BCC) and face-centered cubic (FCC) lattice materials were established by using Timoshenko beam model, and the flexibility matrix of lattice materials was determined. The effect of nodal and shear on the Young's modulus of lattice materials was analyzed. The results show that the theoretical model is in good agreement with the finite element numerical simulation. Moreover, the lattice nodal has a great influence on the equivalent Young's modulus and shear modulus of BCC and FCC lattices, and the elastic properties of lattice materials will be underestimated if the nodal effect is ignored. FCC has a higher specific Young's modulus than BCC lattice, while BCC has a higher specific shear modulus than FCC lattice. Furthermore, FCC lattice materials have higher compression stiffness than most of lattice materials.